Measuring the service quality of airline services in Malaysia - Abdullah, Kalthom; Abd. Manaf, Noor Hazilah; Mohd. Noor, Kamariah (IIUM Press, 2007)
The perception of Malaysian consumers of the quality of airline services was examined in this study using the SERVQUAL measurement. The results of the study indicate that the most significant factors in Malaysian customers’ perception of service quality are Empathy, Tangibles and Assurance. In addition, the respondents indicated that the airlines surveyed performed better than expected on the Responsiveness dimension of service quality. There is also a strong indication that satisfaction with service quality results in future use and the likelihood of recommending the airline to others.